Identification of a new species, Trichia macrospora, and a newly recorded species, T. flavicoma (Myxogastria), in China - Bo, Zhang; Yu, Li (Phytotaxa, 2016)
A new species, Trichia macrospora, collected in Jiangxi province, China, is described herein. Trichia macrospora has larger (about 17–19 μm in diam.) densely verrucose spores than other described species of Trichia, with abundant long, slim spinulations. We present a scanning electron micrograph study of the species and a key to the genera of the species. Holotype specimens of T. macrospora are deposited in the herbarium of the Mycological Institute of Jilin Agricultural University (HMJAU), Changchun, China. We also report a new record of a species of Trichia, T. flavicoma (Lister) Ing, in this paper, specimens of which are deposited in the HMJAU.